MEMAHAMI PERAN, HAK DAN MARTABAT PEREMPUAN DALAM PANDANGAN KONSEPTUAL DAN GENERASI Z - Akhnalia Izzal millah; Arina Maula; Harnum Diastuti (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2024)
The main aim of this article is to analyze the role, rights and dignity of women in the social changes that occurred from the time of the Prophet Muhammad to the present, as well as to describe how they contribute to shaping social transformation in society. This approach allows us to gain a comprehensive understanding of the role of women in specific social and historical contexts. The results of the analysis show that women play an important role in the process of social reform. Women also play an important role in supporting changes in social norms, including gender equality and the protection of women's rights.